Assistance to twins at risk of congenital COVID-19 infection, experience report (Research, Society and Development, 2020)
This study aimed to describe the assistance and characterize the clinical evolution of premature twins at risk of congenital infection, born to a mother infected with SARS-CoV-2 and with a clinical picture of COVID-19. It is an experience report described from the medical records of the twins and their mother. Premature twins, gestational age 28 weeks and three days, both male. The twin I weighed 1050 grams and the second, 698 grams. At 36h of life, collection was performed by means of swab of oro and nasopharynx, of both, for RT-PCR research for SARS-CoV-2, positive in both. Twin I died after 48 hours of life and II stayed in the Neonatal Intensive Care Unit for more than 2 months. There was no contact of the mother with the twins at the moment of birth until the fifteenth day of life of the twin II, there was also no breastfeeding during this period. New RT-PCR research for SARS-CoV-2 and rapid test performed on the fifteenth day of life were negative. The possibility of mother-to-child transmission and the consequences that this virus can cause on the fetus is worrying. However, there are several reports that suggest a low potential for this transmission, yet this possibility cannot be ruled out and must be ensured by adequate assistance with trained staff and all transmission care taken after birth.